Fatty acid of moringa oleifera oil at different sample condition - Muhammad Norazan , Abu Hassan (2013)
Moringa oleifera (M.O) is widely known as the miracle tree which has been recognized as one of the possible resources that can produces biodiesel using a transesterification process supported with a base catalyst. Theoretically, most of the research on the fatty acid in M.O oil is based on dry sample seed and there is no information about the fatty acid on M.O oil that can be affected by fungus or still in growth. Hence, by manipulating the sample condition into three parts, the extraction of M.O seed begins by extraction process using thermal soxhlet with hexane as a solvent and all the samples went through transesterification process in order to measure the unknown fatty acid in each sample. The fatty acid is measured using a Gas Chromatography Mass Spectrometer GC-MS. In sample A, B, C, D, E and F the highest percentage area among the two trials is 49.95, 48.87, 54.56, 49.35, 27.32 and 40.05 respectively. Mean while, the retention time for sample A, B, C, D, E and F is at 32.510, 32.510, 32.467, 38.495, 32.478 and 32.483 respectively. It is expected the fatty acid for sample B and E is different as it affected by fungus but the result showed that the fatty acid is the same for the sample dry, wet and effected condition. In the analysis also there is Stearic acid and Palmitic acid that is also commonly find in the vegetables oil. As a conclusion sample A, B, C, D, E and F have a common acid same as the exact fatty acid in the biodiesel. However, the result shows there are additional of unknown fatty acid exist such as Margaric acid and Arachidic acid. Even all the samples have the same fatty acid component, but their oil content is different. The dry sample and the affected has a common oil content while the wet sample shows vice versa because most of it has high moisture content